How Do Asymmetric Information and Financial Factors Influence Earnings Management? - Hamzah, Amir; Nopiyanti, Hilda (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
The purpose of this study is to analyze the influence of information asymmetry, deferred tax assets, deferred tax expenses, free cash flow, and investment opportunities set on earnings management practices in consumer service sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2017-2021. This research uses a descriptive and verificative method with a population of 47 companies. Through the purposive sampling technique, this research selects 22 companies for the period 2017-2021, resulting in a total of 110 observation data. The analysis method used is Panel Data Regression, which involves stages of classic assumption, model estimation, and model selection testing, as well as the coefficient of determination, and hypothesis testing. The partial testing results show that all observed variables have a positive and significant impact on earnings management practices. This research provides an important contribution to understanding the dynamics of earnings management practices in the context of the consumer service industry in Indonesia.